Sports infrastructure in the era of global transformations: rethinking approaches to public governance amidst multiple risks - Kushnir , Volodymyr (Pressing Problems of Public Administration, 2024)
This article addresses the pressing issue of public governance of sports infrastructure in an era of global change. The author analyzes the impact of technological, social, geopolitical, and value-based transformations on the state, functions, and requirements of sports facilities. The article highlights the growing public expectations regarding the quality and functionality of infrastructure, the intensifying competition among countries for prestigious sporting events, and the increasing role of the private sector in financing the industry. At the same time, traditional management approaches are proving inadequate due to excessive budget expenditures, lack of transparency, and vulnerability to security threats. The article systematizes the key challenges for Ukraine, including the destruction of infrastructure due to Russian aggression, corruption risks, high maintenance costs, and damage from hybrid threats. It emphasizes the need to develop a comprehensive Strategy for the industry’s development based on transparency, inclusivity, and resilience. Priority areas for modernization include implementing «green» technologies, flexible architectural solutions, public-private partnership (PPP) models, digital security platforms, and public control mechanisms. The application of emergency engineering and military logistics approaches in rebuilding damaged facilities is also considered promising. The author concludes that the systematic implementation of global best practices can transform Ukrainian sports infrastructure from a post-Soviet burden into a driver of national development. However, the main condition for success lies in changing the management philosophy in favor of creating public value, stakeholder collaboration, and the active formation of a sustainable ecosystem for the industry’s development.